The ethical concerns of the fast fashion consumer: a gender perspective - Colnago, Quéren Clemente (2019)
Consumer behavior is been studied by academia since the late fifties. Despite the advances seen in the area, the topic still not fully explored due to the big range of variables that can influence consumers and their shopping practices. The fast fashion model is the main disruption experienced by the fashion sector in the past decades. Despite being surrounded by social and environmental scandals, companies adopting this business model present a solid growth and profitability over the years allowing some of them to be classified as the biggest apparel companies in the world. This paper aimed to explore the reasons why consumers keep buying from fast fashion companies even with these scandals being frequently reported by media. From the Literature Review, emerged the fact that there is no consensus amongst scholars if gender can influence the ethical concerns during the shopping experience. Therefore, the paper focused on exploring the ethical concerns and behaviors of fast fashion consumers under a gender perspective. Females and males were compared in five topics, being (i) the most important factor to consider when buying a fast fashion piece, (ii) the self-proclaimed concern about social and environmental impacts generated by the fast fashion industry, (iii) prior consideration to stop buying from fast fashion due to the social and environmental impacts produced by these companies, (iv) future consideration to stop buying from fast fashion due to human rights violation and (v) beliefs about the impacts generated by fast fashion companies in the countries where the clothes are produced. The results of the survey show no significant difference between the two groups, supporting past findings that also aimed to compare women and men in regards of their ethical concerns and shopping modes.